Ticket of admission to a party meeting, on 29 September 1932, in commemoration of the fact that two years ago the masses were called for technical inventions (1932)
Ticket of admission to a party meeting, on 29 September 1932, in commemoration of the fact that two years ago the masses were called for technical inventions.